Ferrocenyl chalcones with phenolic and pyridyl anchors as potential sensitizers in dye-sensitized solar cells. Issue 100 (13th October 2016) - Chauhan, Ratna; Yadav, Reena; Singh, Ashish Kumar; Trivedi, Manoj; Kociok-Köhn, Gabriele; Kumar, Abhinav; Gosavi, Suresh; Rane, Sunit
Abstract : Five ferrocenyl chalcones with phenolic and pyridyl anchors were prepared and their light harvesting properties explored in dye-sensitized solar cells (DSSCs). Abstract : Five ferrocenyl chalcones viz. ( E )-1-(3′-hydroxyphenyl)-3-ferrocenylprop-2-en-1-one (H-1 ), ( E )-1-(4′-hydroxyphenyl)-3-ferrocenylprop-2-en-1-one (H-2 ), ( E )-1-(2′-hydroxyphenyl)-3-ferrocenylprop-2-en-1-one (H-3 ), ( E )-1-(4-pyridyl)-3-ferrocenylprop-2-en-1-one (H-4 ) and ( E )-1-(2-pyridyl)-3-ferrocenylprop-2-en-1-one (H-5 ) having hydroxyl or pyridyl as the anchoring group have been synthesized and characterized using microanalyses, IR, 1 H and 13 C NMR, and in three cases, using single-crystal X-ray diffraction. UV-vis spectroscopic studies indicates that in comparison to ferrocene the electronic absorption bands of the synthesized dyesH-1–H-5 are bathochromically shifted up to 530 nm with concomitant enhancement in their intensities. The synthesized dyes have been exploited as photosensitizers in TiO2 -based dye-sensitized solar cells (DSSCs). The photovoltaic performances and charge transport properties (EIS spectra) were studied to evaluate the synthesized dye performances in DSSCs. Amongst all the ferrocenyl chalcone dyes, those with the hydroxyl linkerH-1–H-3 showed relatively superior photovoltaic performance in comparison to the dyes having a pyridyl anchor. The superior performances ofH-1–H-3 are probably due to the better electronic communication between the ferrocene and the six-membered aromatic ring with anchoring group as well as the high dye loading abilities of these compounds on the TiO2 surface, which suppress charge recombination, prolong electron lifetime, and decreases the total resistance of DSSCs. The assembly fabricated usingH-2 showed the best performance with an overall conversion efficiency η of 6.55%, J sc of 11.99 mA cm −2 and V oc of −0.74 V. The long term stability of the photocurrent output of the cell usingH-2 as photosensitizer has been monitored during 700 h which shows 92% retention of the cell parameters. Also, H-2 showed better thermal stability than the state-of-the-artN719 dye and also has a comparable lifetime of electrons in the conduction band.